94 Trends in cannabis use, health effects, and criminalization prior to cannabis legalization in Michigan. (5th May 2020) - Kamat, Sonia; Bohnert, Kipling M; Bonar, Erin E
Abstract : Statement of Purpose: In 2018, Michigan was the 10th state to pass a recreational cannabis law. The purpose of this report is to provide insight into cannabis-related indicators before recreational cannabis laws were enacted, and serve as the baseline for future evaluations following cannabis legalization in Michigan. Methods/Approach: Existing data were compiled across areas (e.g., use, hospitalizations, legal charges, etc.) that potentially affect the public's health and well-being. The report notes key findings, highlights data limitations, and elaborates priorities for tracking cannabis-related trends over time. Results: An estimated one in nine Michigan residents (11.6%) used cannabis in the past month, which has increased by over 60% from 2002–2003 to 2016–2017. Overall, the rate of annual fatal motor vehicle crashes per 100 million vehicle mile traveled decreased from 1.04 in 2004 to 0.92 in 2017, while the number of drug tests administered to drivers of fatal crashes doubled simultaneously. The rate of hospitalizations for cannabis poisoning increased from 2010 (2.5 per 100, 000 persons) to 2017 (3.7 per 100, 000 persons). Cannabis-related legal charges increased by 2.4% from 2012 to 2018, peaking in 2016. However, the percentage of cannabis-related convictions out of all criminal convictions was highest in 2014 (4.2%) and lowest in 2018 (3.2%). Conclusions: Cannabis use prevalence is higher in Michigan than in the Midwest and the United States. Better characterization of the potential involvement of cannabis in driving-related outcomes is needed. Data on cannabis-related hospitalizations highlight the need for prevention programs focusing on reducing poisonings, especially as higher potency cannabis-containing products become available. Changes in cannabis-related criminal justice data warrant monitoring over time. Significance and Contributions to Injury and Violence Prevention Science: Examining changes in cannabis-related indicators over time will allow stakeholders and public health officials to best understand the potential impacts of recreational cannabis on public health and well-being. Funded by: The Center for Disease Control and Prevention R49 CE002099